A comparative analysis of remdesivir and other repurposed antivirals against SARS‐CoV‐2. Issue 1 (3rd November 2020) - Simonis, Alexander; Theobald, Sebastian J; Fätkenheuer, Gerd; Rybniker, Jan; Malin, Jakob J
Abstract: The ongoing SARS‐CoV‐2 pandemic stresses the need for effective antiviral drugs that can quickly be applied in order to reduce morbidity, mortality, and ideally viral transmission. By repurposing of broadly active antiviral drugs and compounds that are known to inhibit viral replication of related viruses, several advances could be made in the development of treatment strategies against COVID‐19. The nucleoside analog remdesivir, which is known for its potent in vitro activity against Ebolavirus and other RNA viruses, was recently shown to reduce the time to recovery in patients with severe COVID‐19. It is to date the only approved antiviral for treating COVID‐19. Here, we provide a mechanism and evidence‐based comparative review of remdesivir and other repurposed drugs with proven in vitro activity against SARS‐CoV‐2. Abstract : This comprehensive review discusses preclinical and clinical outcomes of remdesivir and other repurposed antiviral drugs against SARS‐CoV‐2.